Back to nature? Attention restoration theory and the restorative effects of nature contact in prison. (May 2019) - Moran, Dominique
Abstract: This paper considers the potential for elements of custodial environments to have a restorative effect on those who are incarcerated within them. Considering the applicability and practicality of using Attention Restoration Theory (ART) to frame experience in a custodial context, it interprets results of a survey of prisoners at a large medium-security prison for men in the United Kingdom. It reflects on prisoners' experiences in relation to elements of the environment in which they reside; specifically, outdoor green spaces and green views in the form of whole-wall photographic images of the natural environment. In an otherwise stressful context, such elements were self-reported to enable restorative effects, and to increase feelings of calm, and the ability to reflect. It finds that the potential benefits differed between environmental elements, and that compatibility with prisoners' own needs was a key issue. It concludes with suggestions about the potential utility of ART-informed design of custodial landscapes. The paper also reflects on the methodological challenges of using ART to understand the experience of prisoners. Highlights: Nature contact delivers health benefits in a range of settings. Potential benefits of nature contact for prison inmates remain under-researched. Attention restoration theory was applied to explore the experience of prisoners' access to green space and images of nature. Nature contact appears to relieve mental fatigue in up to two thirds of those surveyed. Some prisoners believe that the available nature helps them to feel calm and clear their minds.